COVID-19 Dalam Perspektif Masyarakat dan Ajaran Islam - Tjatur Prijambodo (Universitas Muhammadiyah Surabaya, 2020)
AbstractCOVID-19 (Corona Virus Disease 2019) is a respiratory infection caused by a newcoronavirus, SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2). Currently,COVID-19 has spread throughout the world, including Indonesia. COVID-19 disease cancause mild to severe symptoms. Corona Virus Infection is influenced by three things; host,infectious agent and environment. Covid-19 not only affects the health sector, but also variousfields such as education, economics, social and others. Therefore it is important to contributein overcoming the Covid-19 disease. With a correct understanding of the Covid-19 Pandemic,apart from the Government, community participation is needed to reduce transmission. Publicunderstanding is the key to the success or failure of steps taken by the Government as a policymaker. The attitude of a Muslim towards this Pandemic cannot be separated from Islamic Law(Al Quran and Hadith). Currently, many of us are panicked by the pandemic outbreak. Do notlet the fear of Covid-19 exceed or even overcome our fear of Allah. Yet it is Allah who createdand Allah is the one who has the power to uproot what he has created in His will.Keywords; Covid-19, understanding, Islamic Law